2020
DOI: 10.1177/0084672420909436
|View full text |Cite
|
Sign up to set email alerts
|

Emotional bonds: Bridging the gap between evolutionary and humanistic accounts of religious belief

Abstract: Recent years have seen a growing willingness in the evolutionary cognitive science of religion (ECSR) to embrace an inclusive, theoretically pluralistic approach and the emergence of a broad consensus around some key themes that collectively constitute a central theoretical core of the field. Nevertheless, ECSR still raises serious problems for some in the humanities. In exploring the reasons for the perception of conflict between humanistic and cognitive evolutionary approaches to religion, I suggest that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…It would be a mistake to consider social systems as something very different from their evolutionary predecessors. Thus, humans demonstrate the most complicated social interactions, in which analogs and prerequisites can be found in many species [ 129 ], but first of all in primates [ 18 ]. It has been reported that sharing emotional states such as anxiety is an effective strategy of communication in a group because it reduces the time of detecting the danger and thus increases the chances for survival of any individual [ 114 ].…”
Section: Results Of Considering Subjective Reality Within the Evoluti...mentioning
confidence: 99%
“…It would be a mistake to consider social systems as something very different from their evolutionary predecessors. Thus, humans demonstrate the most complicated social interactions, in which analogs and prerequisites can be found in many species [ 129 ], but first of all in primates [ 18 ]. It has been reported that sharing emotional states such as anxiety is an effective strategy of communication in a group because it reduces the time of detecting the danger and thus increases the chances for survival of any individual [ 114 ].…”
Section: Results Of Considering Subjective Reality Within the Evoluti...mentioning
confidence: 99%